UJI AKTIVITAS ANTIPLASMODIUM FRAKSI N-HEKSANA DAUN Peronema canescens TERHADAP Mus musculus - Fenny Andriani; Agus Sundaryono; Nurhamidah Nurhamidah (University of Bengkulu, 2017)
Peronema canescens (Sungkai) has been used in Bengkulu as raw herbal remedy to reduce the fever, some people are using as a malaria drug. P. canescens leaves contain alkaloids, flavonoids, tannins and terpenoids – steroids .This study aims to analyze the effect of P. canescens leaves n-hexane fraction. against paracetemias in Mus musculus infected with Plasmodium berghei, then to prove whether the . P. canescens leaves n-hexane fraction has potential as alternative medicine for malaria . To make P. canescens extract , leaves was macerated using EtOH (96%), then filtrate was evaporated using a rotary evaporator, then fractionated with n-hexane. The 25 healthy M.musculus weighing 20-40g each, infected with P.berghei, grouped into 5 ie group 1 (K-) was treated orally with aquades, group 2 (K +) was treated orally with 0.42 mg of Chloroquine, Group 3 (P1) Group 4 (P2), group 5 (P3) was treated orally with a P. canescens leaves n-hexane fraction each at a dose of 0.028 , 0.056 and 0.084 g / kgBW. After 3 days of digestion for each treatment, the amount of erythrocytes was calculated under a microscope. : The giving of the with dose 0,028 g / kgBW able to inhibit paracetemia 33,49%, 0,056 g / kgBW able to 57.91% and 0,084 g / kgBW able to 61.69% The conclusion is the P. canescens leaves n-hexane fraction at a dose of 0.028 , 0.056 , and 0.084 g / kgBW orally wil be decreased the amount of paracetemia in M.musculus, and the higher the dose given the higher percent of the inhibition.